A RARE AUTOPSY FINDING – “ABSENCE OF SAGITTAL SUTURE” (Journal of Forensic Medicine & Toxicology, 2024)
The cranial sutures and their development is the most interesting in the field of cranial growing and shaping. Majority of Skull bones are held together by fibrous joints termed as sutures. The bones of the skull have two layers, the tabula interna and externa, which are separated by a vascular spongy bone space (diploe). These bones are separated by sutures which, in a series, are analogous to the epiphyseo-diaphyseal planes that in both are loci of growth, and that both have a sequence of timing and union . In this case I have found absence of sagittal suture which was of normal shape with no saphocephaly. From above it can be concluded that Absence of the sagittal suture does not result in scaphocephaly.
Keywords: development; scaphocephaly; skeleton; horoscope